Efficient Transient Analysis for Large Locally Nonlinear Structures - Joshua H. Gordis; Jeffrey Radwick (Shock and Vibration)
A general and exact theory for transient structural synthesis is extended to address structural systems with an arbitrary number of localized sources of structural dynamic nonlinearity. The formulation is independent of model size, in that only those model degrees-of-freedom of interest need be retained in the synthesis. The theory provides for the efficient calculation of nonlinear transient response due to externally applied loads and prescribed base motions. The theory can function as a substructure coupling and structural modification procedure allowing structural nonlinearities to be isolated from the remaining linear substructures, which are solved once. The nonlinear synthesis in effect installs the nonlinear elements and calculates the nonlinear transient response. An example demonstrate the order of magnitude decrease in time required, as compared to traditional direct integration.